PERFORMANCE OF AMARANTH (AMARANTHUS CRUENTUS) AS INFLUENCED BY NPK FERTILIZER AND ORGANIC LIQUID FERTILIZER AT SAMARU, NORTHERN GUINEA SAVANNA OF NIGERIA - Luka, G. I.; Ibrahim, U.; Rabo, M. (FUDMA JOURNAL OF SCIENCES, 2023)
Organic fertilizers have been proven to be more affordable, increase yields and safer for the ecosystem compared to chemical fertilizers. A study was carried out on the effect of NPK fertilizer and an organic liquid fertilizer (SuperGro) on Amaranthus cruentus in 2019 at the research field of the Institute for Agricultural Research and in 2022 at the Teaching and Research Farm of Samaru College of Agriculture, Ahmadu Bello University, Zaria in the northern guinea Savannah of Nigeria. SuperGro liquid fertilizer is 100% organic, made from poultry droppings and seabird guano. It contains (72 g L-1 N), (45 g L-1 P, 30 g L-1 K, 15 g L-1 S, 9 g L-1 Ca, 7 g L-1 Mg), micronutrients (5 mg L-1 Fe, 3 mg L-1 I, 1 mg L-1 Zn and 1 mg L-1 of marine salts.  Treatments consisted of NPK 20:10:10 at 150, 300, 450 and 600 kg ha-1, SuperGro at 0.5, 1.0 and 1.5 L ha-1and a control plot (Zero fertilizer) laid out in a randomized complete block design with three replications. Data was collected on plant height, leaf area index, foliage yield and seed yield and were subjected to analysis of variance using the general linear model procedure of the statistical analysis system package. Results obtained showed that application of either of the fertilizers increased the parameters taken. However, foliage yield was highest with application of 1 L ha-1 of SuperGro where 75,556 kg ha-1 was obtained in 2019 and 86,632 kg ha-1 in 2022...
Keywords: Amaranth; NPK Fertilizer; Organic Liquid Fertilizer; Samaru